The phenotypic spectrum of X‐linked, infantile onset ALG13‐related developmental and epileptic encephalopathy. (7th January 2021) - Datta, Alexandre N.; Bahi‐Buisson, Nadia; Bienvenu, Thierry; Buerki, Sarah E.; Gardiner, Fiona; Cross, J. Helen; Heron, Bénédicte; Kaminska, Anna; Korff, Christian M.; Lepine, Anne; Lesca, Gaetan; McTague, Amy; et al.
Abstract: Objective: Asparagine‐linked glycosylation 13 ( ALG13 ) deficiencies have been repeatedly described in the literature with the clinical phenotype of a developmental and epileptic encephalopathy (DEE). Most cases were females carrying the recurrent ALG13 de novo variant, p.(Asn107Ser), with normal transferrin electrophoresis. Methods: We delineate the phenotypic spectrum of 38 individuals, 37 girls and one boy, 16 of them novel and 22 published, with the most common pathogenic ALG13 variant p.(Asn107Ser) and additionally report the phenotype of three individuals carrying other likely pathogenic ALG13 variants. Results: The phenotypic spectrum often comprised pharmacoresistant epilepsy with epileptic spasms, mostly with onset within the first 6 months of life and with spasm persistence in one‐half of the cases. Tonic seizures were the most prevalent additional seizure type. Electroencephalography showed hypsarrhythmia and at a later stage of the disease in one‐third of all cases paroxysms of fast activity with electrodecrement. ALG13 ‐related DEE was usually associated with severe to profound developmental delay; ambulation was acquired by one‐third of the cases, whereas purposeful hand use was sparse or completely absent. Hand stereotypies and dyskinetic movements including dystonia or choreoathetosis were relatively frequent. Verbal communication skills were absent or poor, and eye contact and pursuit were often impaired. Significance: X‐linked ALG13 ‐related DEE usually manifests as West syndrome with severe to profound developmental delay. It is predominantly caused by the recurrent de novo missense variant p.(Asn107Ser). Comprehensive functional studies will be able to prove or disprove an association with congenital disorder of glycosylation.